Forecasting of Intraregional Unevenness of Economic Development of the Region - Alexander Evgenyevich Chepik (Управленческое консультирование)
When studying a problem of intraregional unevenness of economic development, one of the main objectives of statistical research is forecasting of dynamics of development of dissimilarity. In the article it is offered to estimate unevenness of intraregional economic development by means of an unevenness index. Research of this indicator on materials of the Republic of Buryatia allowed to study its dynamics and to choose an adequate method of creation of trend models. On the basis of the received equations of regression the medium-term forecast of intraregional dissimilarity in the region which is recommended for use in practice of management of regional development was calculated.